Gamified Digital Learning with Learning Analytics in Madrasah Tsanawiyah: Effects on Motivation, Engagement, and Learning Outcomes at MTs Sunan Gunung Jati Kismantoro Wonogiri - Sukarno Sukarno; Izzah Al Fawaidah (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective – This study aims to examine the effectiveness of gamified digital learning integrated with learning analytics in enhancing students’ learning motivation, engagement, and learning outcomes in Islamic education at the junior secondary level. Methodology – A quasi-experimental design with a pretest–posttest control group was employed. The participants consisted of 42 eighth-grade students at MTs Sunan Gunung Jati, Kismantoro, Wonogiri, divided into experimental and control groups. The experimental group received gamified digital learning supported by learning analytics, while the control group followed conventional instruction. Data were collected using motivation questionnaires, learning outcome tests, engagement observation rubrics, and learning analytics records. Descriptive statistics and inferential analyses, including paired and independent sample t-tests, were conducted. Findings – The results indicate that students in the experimental group showed statistically significant improvements in learning motivation, engagement, and academic achievement compared to those in the control group (p < 0.05). Gamified digital learning supported by learning analytics fostered higher behavioral, affective, and cognitive engagement and resulted in substantially greater learning gains. Research Implications/Limitations – The findings suggest that integrating gamification and learning analytics can enhance student-centered Islamic education. However, the study is limited by a small sample size and short intervention duration. Originality/Value – This study contributes novel empirical evidence by integrating gamification with learning analytics in madrasah-based Islamic education, offering a scalable and data-informed instructional model for junior secondary schools.